Shared Memories, Shared Stories: How Memorable Travel Experiences, Destination Attachment, and Tourist Satisfaction Drive sWOM Intentions - Octaviani, Natasya; Yudhistira, Putu Gde Arie (Universitas Brawijaya, Indonesia, 2024)
Social media has become an important platform for sharing travel experiences, where information tourists share can influence prospective tourists' perceptions and decision-making processes. Understanding what motivates tourists, particularly Generation Z tourists, to share their experiences on social media is critical for destinations and marketers. This study investigates the influence of memorable travel experiences on social word-of-mouth (sWOM) intentions of Generation Z tourists in Indonesia through the mediating roles of destination attachment and tourist satisfaction. Additionally, this study examines how positive emotions moderate the relationship between memorable travel experiences on both mediators. This quantitative study used purposive sampling to collect data from 519 Indonesian Generation Z tourists, which was then analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The findings show that memorable travel experience directly influences sWOM intentions. Destination attachment and tourist satisfaction positively mediate the relationship between MTE and sWOM Intention. However, the moderating effect of positive emotions was not supported, indicating that positive emotions did not strengthen the relationship between memorable travel experiences and the two mediators. This study is beneficial for tourism practitioners, as understanding these dynamics can help enhance sWOM intentions and optimize positive online recommendations to attract and retain Generation Z tourists.